Hepatitis C in A Child with Thalassemia - Dina Dina; Anky Tri Rini; M. Widia; Sudaryat S. (Indonesian Pediatric Society, 1995)
We present a case of hepatitis C in a patient with thalassemia major. The transmission seems to be through blood transfusion. The diagnosis of hepatitis C was determined by the presence of anti HCV in serum. Ursodeoxycholic acid therapy gave a satisfactory result and the patient was discharged after showing improvement of both clinical signs and liver function tests. He was suggested for regular examination to evaluate anti HCV and his thalassemia. lt is believed that if anti HCV titer is more than 6 months, hepatitis may become chronic hepatitis C.